Study of Cross Sections for 10 Li 10 Reaction From Cross Sections of Li a,n) Reaction Using the Reciprocity Theory for the Ground State - Youhana, H. M.; Sarsam, M. N.; Ebrahiem, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, light elements Li ,10B for (a,n) and (n,a) reactionsas well as o-particle energy from threshold energy to 10 MeV areused according to the available data of reaction cross sections. Themore recent cross sections data of (a,n) and (n,a) reactions arereproduced in fine steps 42 Kev for 10B(n,o) Li in the specifiedenergy range, as well as cross section (o,n) Values were derived fromthe published data of (n,a) as a function of a-energy in the same fineenergy steps by using the principle inverse reactions. This calculationinvolves only the ground state of Li OB in the reactions 'Li(a,n) BB (n,a) LiIntroductionWhen two charged nuclei overcome their Coulomb repulsion, arearrangement of the constituents of the nucleus may occur. Similarto the rearrangement of atoms in reacting molecules during a chemicalreaction this may result aa nuclear reactiontargetNuclear reactions are usually produced by bombarding a ornucleus with a nuclear projectile in most cases a nucleon (neutron proton) or a light nucleus such as a deuteron or an majority of nuclearAt low excitation energies 10 MeV),the reactions involve the formation of two nucleione nearly equal incharge and mass number to the target nucleus. Such reactions arerepresented by an equation of the typebX athe lab. System)Where X target (at rest in bombarding particle